Locus of Control in Offenders Returning to Crime and Their Perception of Their Own Families of Origin - Nowak, Beata Maria (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
Subjectively perceived locus of control provides information on the extent of individual adaptation and how the individual deals with difficulties in various spheres of life. Learning to perceive the connection between our behavior, its positive and negative effects and taking measures to achieve the desired effect is the result of repeated experience. Family factors are crucial for shaping the locus of control, i.e. parental attitude, the relationship between a child and their parents and the child’s experience in various socio-educational situations. This article presents the results of a survey on locus of control in penitentiary recidivists and their perception of selected aspects of upbringing in their families of origin. The survey uses J.B. Rotter’s Locus of Control Scale translated by L. Drwal’s, and the author’s own questionnaire. The participants of the survey were 245 recidivists and penitentiary multi-recidivist offenders in two types of penitentiaries – semi-open and closed. It was established that the penitentiary recidivists have an external locus of control. There were, however, no significant associations between locus of control and a type of family of origin as well as the number of repeated offences. Penitentiary recidivists perceive their own families of origin as having numerous problems and the characteristics which were probably the cause of the formation of an external locus of control (i.a. unemployment, poverty, alcoholism in the family and helplessness or passivity of parents in the face of growing problems, dominant, parental attitude with an adverse effect on upbringing: ‘lukewarm’ – indifferent and rejecting, and ‘unstable’ – inconsistent attitude. In addition, the survey showed that the higher the level of education of the person imprisoned, the worse the relationship with their parents. The survey results indicate the need for providing both social and social development support for the families with penitentiary problems. It is also desirable to take preventive, psycho-educational and resocialisation actions, focused on reorienting LOC of penitentiary recidivists from an external to an internal one. In addition, there should be parenting skills workshops and certain measures in the field of shaping parental attitudes should be taken in order to prepare inmates for living outside prison bars.